The effect of balanced scorecard on business performance : a mediating effect of new product development success in food and beverage industry in Malaysia - Zhengxiaoming, Aminaimu (2020)
This study was conducted to understand the core problems facing food and beverage industry suppliers in competing with other suppliers to fulfill customer requirements. Every supplier company needs to have its own identity value to maintain itself in the food and beverage industry. Recently, Balanced Scorecards (BSC) have been used to evaluate performance. The existence of great competition in the food and beverage industry in Malaysia has lead to a need for the development of new successful and strategic products to increase company performance. In this study, the impact of balanced scorecards on company performance in the food and beverage industry is investigated. The effects of new product development success on company performance was evaluated using four perspectives, which were the finance perspective, customer perspectives, internal process perspective, and learning and growth perspective. The theory used in this study was the Resource Based View (RBV) theory. RBV theory was useful in evaluating company performance. Data collection in this study used a quantitative survey questionnaire which target production managers in food and beverage industry in Malaysia. 209 respondents answered the survey. Most respondents were production managers with less than five years of experience in the food and beverage industry in Malaysia. The theoretical framework was created based on previous literature and model validity was measure using Smart PLS 3.2.8. The PLS–SEM algorithm showed the highest outer loading value, which invariably met the threshold cut off value. Validity and reliability tests showed satisfactory results. The study results show that the financial, internal process, and customer perspectives had a positive and significant effect on new product development success. The learning and growth perspectives had a smaller t-value, showing no significant effect on new product development success. The overall hypotheses in this study showed that new product development success mediated between the financial perspective, internal process perspective, customer perspective, and learning and growth perspective and organization performance. The outcomes of this study can assist food and beverage companies in improving their ability to meet market demands. Extension of this research may incorporate an individual scope as most producers adapt knowledge gained from working experts.